Nematodes associated with terrestrial slugs in the Edmonton region of Alberta, Canada. (13th October 2020) - Brophy, T.; Mc Donnell, R.J.; Howe, D.K.; Denver, D.R.; Ross, J.L.; Luong, L.T.
Abstract: A survey of nematodes associated with terrestrial slugs was conducted in residential gardens, nurseries, greenhouses and agricultural sites located in and around Edmonton, Alberta, Canada. A total of 2406 slugs were collected from 82 sites. Slugs were decapitated and cadavers were incubated for two weeks, with emerging nematodes removed and processed for identification. Nematodes were identified using molecular sequence data for the 18S ribosomal DNA. Nematodes were recovered from 20 of the 82 sites surveyed, with 24.4% of the slugs infected with nematodes. A total of seven nematodes were identified to species level, including Caenorhabditis elegans, Panagrolaimus papillosus, Pellioditis typica, Pelodera pseudoteres, Rhabditella axei, Rhabditoides inermiformis and Phasmarhabditis californica . An additional four specimens were identified to genus level, including Oscheius sp. (9), Pristionchus sp., Rhabditis sp. and Rhabditophanes sp. (1). The two most common nematode species were C. elegans and P. pseudoteres . The facultative parasite, P. californica, was recovered from a single Arion rufus specimen, collected from a seasonal nursery. To our knowledge, this study represents the first survey of slug-associated nematodes in Canada.